IDDF2022-ABS-0252 Four types of porphyrias diagnosed by physicians from liver disease department: a retrospective study of twelve cases from a single center. (2nd September 2022) - Gan, Weiqiang; Cai, Lirong; Chen, Shuru; Pang, Jiahui; Li, Jianguo; Li, Xinhua
Abstract : Background: The porphyrias are a group of metabolic disorders characterized by deficiencies in the activity of enzymes involved in the biosynthesis of heme. Due to a wide range of clinical symptoms, porphyrias are difficult to diagnose, especially for physicians managing liver diseases. We aimed to improve the understanding of the characteristics of certain porphyrias with the liver involved. Methods: We enrolled twelve patients diagnosed with porphyrias at the Third Affiliated Hospital of Sun Yat-sen University between June 2015 and December 2021. Clinical data, lab findings, histopathological results, and genetic testing were analyzed. Results: Four types of porphyrias were identified among 12 cases, including 6 patients with erythropoietic protoporphyria (EPP, 50%, 6/12), 3 with hereditary coproporphyria (HCP, 25%, 3/12), 2 with variegate porphyria (VP, 16.7%, 2/12) and 1 with porphyria cutanea tarda (PCT, 8.3%, 1/12). There were 10 males and 2 females, with a median age of 27 years at the age of diagnosis. The main symptoms included abdominal pain (66.7%, 8/12), jaundice/pruritus (66.7%, 8/12), photoreactive dermatitis/rash (50%, 6/12), psychiatric disturbance (33.3%, 4/12), ventosity (25%, 3/12), constipation (25%, 3/12). Abnormal transaminases were found in 8 patients (66.7%) with median alanine aminotransferase (ALT) of 68.00 U/L. Hyperbilirubinemia existed in 8 patients (66.7%) with a median total bilirubin of 129.65 μmol/L. Eight of 12 patients had liver biopsies, yellowish brown/brownish yellow/reddish brown granular matters were found to be deposited in capillary bile ducts, hepatocytes or Kupffer cells. Characteristic Maltese cross shapes of birefringent crystalline pigment were found under a polarized light microscope. Eleven of 12 patients had genetic sequencing and two novel FECH mutations (c.605G>A, c.67+1G>C [splicing]), one novel CPOX mutation (c.973A>G) and two novel PPOX mutations (c.454C>T, c.1148T>C) were identified (IDDF2022-ABS-0252 Table 1). Conclusions: Porphyria needs to be considered in patients with cholestasis or jaundice of unknown origin, especially when they have concurrent neuropsychiatric symptoms or skin damage. Liver biopsy and genetic analysis are needed to further support the diagnosis.